Patient Safety Analysis Review Of Nurse's Caring Behavior In Patients With Fall Risk - Ambarika, Rahmania; Novita Ana Anggraini (Universitas STRADA Indonesia, 2021)
Patients with risk of falls is one of the risks of unwanted incidents within the hospital. The risk of the patient falling until an incident has an adverse effect on the patient, one of the adverse effects is the impact of physical injury which includes abrasions, torn wounds, bruises, even in some cases severe falls can result in fractures, bleeding, and head injuries. Objective To find out the relationship between Caring Behavior of Nurses and Patient Safety Risk of Falling. The research method used in the study is cross sectional. The population is all patient patients at risk of falling. The sample size is 67 respondents using purposive sampling technique. Independent variable of research is Caring Behavior. The dependent variable is the Patient safety risk of falling. Data was collected using a questionnaire, then the data were analyzed using the Spearman Rho test. The results showed that the nurse caring nurse was quite good as many as many 35 respondents (52.2%), patient safety risk fell that was enough as many as 30 respondents (4.8%). The results showed that p = 0.000 which means that there is a relationship between Caring Behavior of Nurses and Patient Safety in Falling Risk. Nurse Caring Behavior With Patient Safety The Risk of Falling has a significant relationship, because caring behavior gives direct caring and responsive in each patient condition. 000 which means that there is a relationship between Caring Behavior of Nurses and Patient Safety in Falling Risk. Nurse Caring Behavior With Patient Safety The Risk of Falling has a significant relationship, because caring behavior gives direct caring and responsive in each patient condition. 000 which means that there is a relationship between Caring Behavior of Nurses and Patient Safety in Falling Risk. Nurse Caring Behavior With Patient Safety The Risk of Falling has a significant relationship, because caring behavior gives direct caring and responsive in each patient condition